2016
DOI: 10.1038/ncomms10971
|View full text |Cite
|
Sign up to set email alerts
|

Different states of synaptotagmin regulate evoked versus spontaneous release

Abstract: The tandem C2-domains of synaptotagmin 1 (syt) function as Ca2+-binding modules that trigger exocytosis; in the absence of Ca2+, syt inhibits spontaneous release. Here, we used proline linkers to constrain and alter the relative orientation of these C2-domains. Short poly-proline helices have a period of three, so large changes in the relative disposition of the C2-domains result from changing the length of the poly-proline linker by a single residue. The length of the linker was varied one residue at a time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
83
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(98 citation statements)
references
References 59 publications
15
83
0
Order By: Relevance
“…This premise is consistent with the recent evidence that syt1 exists in two configurations at the synapse: one form promotes vesicle fusion upon stimulation, the other serves to clamp down on spontaneous transmission (Bai et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…This premise is consistent with the recent evidence that syt1 exists in two configurations at the synapse: one form promotes vesicle fusion upon stimulation, the other serves to clamp down on spontaneous transmission (Bai et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Membrane bridging by Syt1 may be further classified to parallel or antiparallel orientations of two C2 domains, i.e., into an oligomerization model and a direct-bridging model [101]; the linking depends on Sty1 interactions with the vesicle and the plasma membrane [32,73]. Parallel and antiparallel orientations of two C2 domains might have different functions, i.e., parallel orientations of the C2A and C2B domain to the plasma membrane trigger vesicle fusion, whereas antiparallel configuration of domains clamp vesicle fusion [104].…”
Section: Model 4: Syt1 Causes Membrane Bridgingmentioning
confidence: 99%
“…The ability to inhibit spontaneous release while stimulating action potential evoked release constitutes the minimal requirements for a machine to synchronize neurotransmitter release with the electrical activity of the releasing cell. The relationship between the two different functions of syt-1 is still not entirely clear, but it has been suggested that the switch from a fusion clamp to a fusion trigger is caused by a change in the relative orientation of the C2 domains (Liu et al 2014b;Bai et al 2016).…”
Section: Synaptotagminmentioning
confidence: 99%